Association of Prenatal Famine Exposure With Inflammatory Markers and Its Impact on Adulthood Liver Function Across Consecutive Generations - Yan, Shiwei; Ruan, Jingqi; Wang, Yu; Xu, Jiaxu; Sun, Changhao; Niu, Yucun (Frontiers in Nutrition, 2022)
Although there has been increasingly recognition that famine exposure in fetal stage damages liver function in adulthood, this deteriorated effect could be extended to the next generation remains vague. This study aimed to explore whether famine exposure was associated with liver function in two consecutive generations, and its association with the mediation role of inflammatory markers. We analyzed the data of 2681 participants from Suihua rural area. According to the date of birth, participants were classified as fetal exposed and nonexposed. The F2 were classified as having no parents exposed to famine, maternal famine exposure, paternal famine exposure or parental famine exposure. In mixed-effect models, prenatal exposure to famine was associated with the elevation of ΔAST (β: 0.22, 95% CI: 0.01, 0.43) and ΔALT (β: 0.41, 95% CI: 0.18, 0.65) levels in F1 adults. Mediation analysis showed that inflammatory markers including serum CRP and TNF-α might mediate the famine-liver function association. This longitudinal data was consisted with the hypothesis that inflammatory markers explained part of the influence of prenatal famine exposure on liver function injury, and the natal mechanism was needed to be elucidated in future study.